Effect of Effleurage Massage On Reducing First-Stage Labor Pain Among Women Giving Birth At Independent Midwifery Practices In Purwakarta Regency, Indonesia - Daris Yolanda Sari; Rika Widiyastuti (International Journal of Health and Pharmaceutical (IJHP), 2026)
Labor pain is a physiological process experienced by every woman during childbirth. Excessive labor pain may increase maternal anxiety, prolong labor, and negatively affect maternal and fetal well-being. Effleurage massage is a non-pharmacological complementary intervention that has been widely used to reduce labor pain because it is simple, safe, inexpensive, and easy to implement in clinical practice. To determine the effect of effleurage massage on reducing first-stage labor pain among women giving birth at independent midwifery practices in Purwakarta Regency. This quantitative study employed a pre-experimental one-group pretest–posttest design. The study was conducted at independent midwifery practices in Purwakarta Regency from October 2025 to Januari 2026. Thirty-three women in the active phase of the first stage of labor were recruited using purposive sampling. Labor pain intensity was assessed using the Numeric Rating Scale (NRS) before and after the effleurage massage intervention. Data were analyzed using the Shapiro–Wilk test for normality and the Wilcoxon Signed-Rank Test with a significance level of 0.05. Before the intervention, 75.8% of participants experienced severe labor pain, while 24.2% experienced moderate pain. After effleurage massage, pain intensity decreased substantially, with 45.5% reporting mild pain, 51.5% moderate pain, and only 3.0% severe pain. The Wilcoxon Signed-Rank Test demonstrated a statistically significant reduction in labor pain following the intervention (p < 0.001). Effleurage massage significantly reduced first-stage labor pain among women giving birth at independent midwifery practices in Purwakarta Regency. This technique may be incorporated into routine midwifery care as an effective complementary non-pharmacological intervention to improve maternal comfort during labor.